Evolving Project ECHO: delivery of pediatric pain core competency learning for interprofessional healthcare providers - C. Lalloo; C. Lalloo; V. Mohabir; F. Campbell; F. Campbell; N. Sun; N. Sun; S. Klein; S. Klein; J. Tyrrell; J. Tyrrell; G. Mesaroli; et al. (Frontiers in Pain Research, 2023)
IntroductionHealthcare providers (HCPs) practicing in community settings are critical to improving access to pain care, yet there are significant gaps in training opportunities designed for interprofessional learners. Project Extension for Community Healthcare Outcomes (Project ECHO®) is an established model for delivering online HCP education through virtual clinics and cultivating a community of practice. However, to our knowledge, the integration of pain core competency education into the ECHO® model has not been previously attempted. This innovation could enhance the ECHO® model while also addressing the growing calls for more accessible interprofessional pain curricula. This paper describes efforts to implement and evaluate core competency curricula within the context of Pediatric Project ECHO for Pain, one of the first pediatric-pain focused ECHO programs in the world.MethodsNeeds assessments informed curricula development. The first delivered core competency model consisted of synchronous webinar-style sessions while the second model included a mixture of asynchronous (eLearning course) and synchronous (virtual clinical debrief) elements. A convenience sample of HCPs was recruited from ECHO program registrants. Participants completed baseline and follow-up surveys to assess core competency acceptability as well as impact on knowledge and self-efficacy related to managing pediatric pain. Usability of the eLearning platform (model 2 only) was also evaluated. Surveys used 5-point Likert scales to capture outcomes. A priori targets included mean scores ≥4/5 for acceptability and ≥80% of learners reporting knowledge and self-efficacy improvements. The study received local research ethics approval.ResultsThe core competency was found to be highly acceptable to interprofessional learners (n = 31) across delivery models, surpassing a priori targets. Specifically, it was characterized as a worthwhile and satisfactory experience that was helpful in supporting learning. The core competency was also associated with improvements in knowledge and self-efficacy by 97% and 90% of learners, respectively. The eLearning platform was reported to have high usability with clinically realistic cases (100% of respondents) that were helpful to inform care delivery (94% of respondents).ConclusionThe integration of core competency learning within the Project ECHO® model was a successful approach to deliver pediatric pain education to interprofessional HCPs.